DAMPAK KENAIKAN HARGA BERAS TERHADAP KONSUMSI KELUARGA PRA SEJAHTERA DI KOTA SURAKARTA - WIWIT RAHAYU (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2010)
Family consumption identified by expenditure allocation for food and non food can be applied for identifying the measure of welfare, with the assumption that the reduction of food consumption percetage upon the total consumption is seen as family prosperity level improvement.